Oral gel loaded with penciclovir-lavender oil nanoemulsion to enhance bioavailability and alleviate pain associated with herpes labialis - Khaled M. Hosny; Amal M. Sindi; Hala M. Alkhalidi; Mallesh Kurakula; Nabil K. Alruwaili; Nabil A. Alhakamy; Walaa A. Abualsunun; Rana B. Bakhaidar; Rahaf H. Bahmdan; Waleed Y. Rizg; Sarah A. Ali; Wesam H. Abdulaal; et al. (Taylor & Francis Group, 2021)
Herpes labialis, caused by herpes simplex virus type 1, is usually characterized by painful skin or mucosal lesions. Penciclovir (PV) tablets are found to be effective against herpes labialis but suffer from poor oral bioavailability. This study aimed to combine the benefits of PV and lavender oil (LO), which exhibits anesthetic activity, in the form of a self-nanoemulsifying drug delivery system (SNEDDS) for the treatment of herpes labialis. Toward this purpose, LO (oil), Labrasol:Labrafil M1944 CS in the ratio of 6:4 (surfactant mixture), and Lauroglycol-FCC (co-surfactant, selected based on the solubility of PV) were evaluated as the independent factors using a distance quadratic mixture design. The formulation was optimized for the minimum globule size and maximum stability index and was determined to contain 14% LO, 40.5% Labrasol:Labrafil 1944 (6:4), and 45.5% Lauroglycol-FCC. The optimized PV-LO-SNEDDS was embedded in chitosan hydrogel and the resulting formulations coded by (O3) were prepared and evaluated. The rheological studies demonstrated a combined pseudoplastic and thixotropic behavior with the highest flux of PV permeation across sheep buccal mucosa. Compared to a marketed 1% PV cream, the O3 formulation exhibited a significantly higher and sustained PV release, nearly twice the PV permeability, and a relative bioavailability of 180%. Overall, results confirm that the O3 formulation can provide an efficient delivery system for PV to reach oral mucosa and subsequent prolonged PV release. Thus, the PV-LO-SNEDDS embedded oral gel is promising and can be further evaluated in clinical settings to establish its therapeutic use in herpes labialis.